Opposing Australia’s First Assisted Immigrants, 1832-42 - Burkett, Melanie. author. aut Link
XIX, 256 p.
Keywords: This book unravels the paradoxical denigration of the first significant group of free (non-convict), working-class emigrants to the Australian colony of New South Wales in the 1830s. Though their labour was sorely needed, the colonial elite rejected the new arrivals on the grounds that they were ‘lazy’ and ‘immoral’. These criticisms stemmed from political, economic, and cultural motivations that ultimately sought to protect, legitimise, and cement the elite’s financial and social hegemony. The author seeks to explore the ulterior motives behind the public denouncements of immigrants by exposing the conflicting and opportunistic rationales used. Brought to Australia from Britain and Ireland through the experiment of ‘government-assisted migration,’ these immigrants are often remembered as ‘brave pioneers’ today, but this book exposes the deep antagonistic attitudes toward immigration that remain entrenched in Australian society. Uncovering early forms of class antagonism in Australia,this book presents useful insights for those researching Australian history and migration studies, as well as scholars of colonial history, by providing a model for re-evaluating and confronting a long-standing pattern in most settler societies: hostility toward immigrants.